La aparente ‘autonomía sustantiva’ del lavado de activos y la necesaria acreditación del delito fuente - Loli Ausejo, Daniel Santiago (2024)
The article 10 of the Legislative Decree 1106 acknowledges the autonomy of the crime of money laundering. A sector of legal doctrine interprets this autonomy as ‘substantive autonomy’, meaning that the predicate offense is not included within the definition of the crime. In response to this stance the author aims to emphasize the significance of the illicit origin as an element of the objective components of the crime of money laundering. Therefore, the author will reinforce the necessity of identifying and proving the predicate offense within the criminal process to properly establish the crime of money laundering. Throughout the text, the author will discuss and interpret relevant legal provisions as well as national jurisprudence to conclude that the autonomy enshrined in Article 10 is limited strictly to procedural autonomy.